Conservação e restauro de esculturas em gesso : valorização, metodologia, ensino - Frade, Marta Alexandra da Costa, 1978- (2019)
The aim of this investigation is to reflect upon the possibility of conceiving and conceptualizing a methodology for the restoration of intervention in plaster sculptures, both movable and immovable heritage. Is it important to esteem plaster artwork? What is its value? Why should one conserve it? Will it have a new use? How should one preserve, conserve and restore it? Considering that there is an increasing preventive concern about movable plaster sculpture collections, that were once produced with a transitory nature, but endured to the present day, different methodologies and results were analysed and compared while trying to understand why sculptures belonging to architectural heritage are undervalued when compared to other types of decorative arts. The main purpose of this investigation is to devise a methodology for intervention, developed from the historic and artistic study the context of the selected case studies, the material under study – plaster – and its conditions, the internal structure study, and the whole investigation of conservation and restoration interventions performed in plaster sculptures. Our intention is to educate the entire academic community with an in situ intervention and to show the results achieved in order to develop a plaster conservation and restoration methodology. The research is arranged in three topics: the appreciation, the methodology for intervention and the importance of education. Thus our intention is to devise an adequate methodology through a theoretical and practical investigation. Finally, there is a documentary file with photographs, videos, charts and inventory record sheets in an effort to encourage the preservation of documentation of each piece of artwork